Prevalence of Sleepiness as a Risk Factor for Road Traffic Accidents: Sample of Hospitalized Saudi Drivers - Siraj O. Wali; Roah A. Merdad (Journal of King Abdulaziz University: Medical Sciences, 2023)
Sleepiness in drivers is an important factor contributing to road traffic accidents. This study aimed to determine the prevalence of sleepiness among car drivers involved in road traffic accidents in Saudi Arabia, and its impact on the accidents. From January to June 2008, all drivers admitted to King Abdulaziz Medical City in Jeddah following their involvement in road traffic accidents, were interviewed within 24 hrs from admission using a questionnaire. Sleepiness was estimated using the Epworth Sleepiness Scale and Stanford Sleepiness Scale. Of all the drivers interviewed, 10.3% reported sleepiness as the main cause of accident; 27.9% reported snoring at night; 47% usually went to sleep after midnight; and 72.1% slept 6 hrs or less per night. Of the drivers with a Stanford Sleepiness Scale of 4-7, 41.1% attributed their accidents to sleepiness, and among drivers with an Epworth Sleepiness Scale of ?10, 70% attributed their accidents to factors other than sleepiness. Most drivers in the study sample had poor sleeping habits, and sleepiness as a risk factor for road traffic accidents was more prevalent when quantified using subjective validated measures.